2001
DOI: 10.1002/med.1009
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin‐proteasome pathway and proteasome inhibitors

Abstract: The ubiquitin-proteasome pathway has emerged as a central player in the regulation of several diverse cellular processes. Here, we describe the important components of this complex biochemical machinery as well as several important cellular substrates targeted by this pathway and examples of human diseases resulting from defects in various components of the ubiquitin-proteasome pathway. In addition, this review covers the chemistry of synthetic and natural proteasome inhibitors, emphasizing their mode of actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
254
0
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(266 citation statements)
references
References 263 publications
4
254
0
8
Order By: Relevance
“…The structural and functional information of proteasomes has allowed the design of small molecules to inhibit its proteolytic activity. These inhibitors, in most of the cases, block the chymotrypsin-like activity of β subunits either reversibly, such as MG132, or irreversibly such as lactacystin and epoxomicin (Kisselev and Goldberg, 2001;Myung et al, 2001).…”
Section: Figure 11: the Ubiquitin-proteasome System (Ups)mentioning
confidence: 99%
See 1 more Smart Citation
“…The structural and functional information of proteasomes has allowed the design of small molecules to inhibit its proteolytic activity. These inhibitors, in most of the cases, block the chymotrypsin-like activity of β subunits either reversibly, such as MG132, or irreversibly such as lactacystin and epoxomicin (Kisselev and Goldberg, 2001;Myung et al, 2001).…”
Section: Figure 11: the Ubiquitin-proteasome System (Ups)mentioning
confidence: 99%
“…Hsp90 is a major cytosolic chaperone and has been shown to refold Fluc upon recovery from heat stress (Schneider et al, 1996). MG132 is a small molecule that reversibly inhibits the chymotrypsin-like activity of the proteasome and hence leads to accumulation of polyubiquitinated proteins in cells which causes proteome stress (Kisselev and Goldberg, 2001;Myung et al, 2001). We measured the effect of proteasome inhibition on Fluc-based sensors by fluorescence microscopy of HeLa cells that were (Figure 29c), which suggests that proteasome inhibition doesn't have a direct influence on the stability of Fluc-EGFP variants and therefore the aggregation of these sensor proteins could be caused by a general proteostasis imbalance.…”
Section: V34 Effect Of Fluc-egfp-based Sensors On the Cytosolic Stmentioning
confidence: 99%
“…Defects in the complex biochemical machinery of UBP signalling pathway are linked to the pathogenesis of many human diseases (Myung et al, 2001). Targeting UBP signalling pathway has therapeutic implication.…”
mentioning
confidence: 99%
“…We have shown that the elimination of RPG1 is correlated with ubiquitination and the requirement of the chymotrypsinlike activity of the catalytic subunits in the 20S proteasome channel (40). Among the E3 ligases that bind the protein to be ubiquitinated, there is one family that recognizes substrates according to the end rule, preferring proteins with basic residues at the N terminus such as R, K, and H (40), often after removal of the N-terminal methionine.…”
Section: Discussionmentioning
confidence: 99%